Carbon emissions disclosure and firm value: A study of firms in Indonesia - Desy Maharani; Inggrite Puspita; Kholidah Suhaimah; Kamalah Saadah (International Journal of Academe and Industry Research)
This study aims to examine the effect of carbon emissions disclosure on firm value in Indonesia using statistical analysis methods. This research uses panel data which consists of a combination of time series and cross section. A total of 1,830 data from 366 Indonesian companies were collected from annual reports and sustainability reports for an observation period from 2018 to 2022 as a sample of the research. Firm value is measured using Tobin’s Q. The results showed that the disclosure of carbon emissions had an effect on firm value. It was also figured out that a control variable, leverage, affected firm value. These results indicate that information about carbon emissions promotes firm value. The disclosure of carbon emissions by the company will affect investors' decisions. This is consistent with the stakeholder theory, according to which investors have the right to obtain information about the company’s activities from annual reports and sustainability reports. Companies are encouraged to foster the initiative to disclose carbon emissions as an effort to reduce the threats of global warming and strengthen stakeholders’ trust in making investment decisions.